Gambaran Dan Persepsi Karyawan Terhadap Budaya Organisasi Di PT. Asuransi Jasa Indonesia Cabang Yogyakarta - Angriani, Dewi (Fakultas Psikologi Universitas Ahmad Dahlan Yogyakarta, 2013)
AbstractÂ This research is a qualitative study aimed to identify the overview organizational culture in PT. Insurance Services Indonesia and determine employee perceptions of organizational cultures that exist in the insurance company. The method used is qualitative case study. Analysis of the data using thematic analysis. Subjects were two employees who have worked more than 15 years were selected using criterion sampling technique. The results showed PT. Insurance Services Yogyakarta Indonesia has a strong organizational culture and can be categorized in the type of fortress because PT. Indonesia Insurance Services is able to maintain the existence of the company as a market leader with an international reputation in the global competitive insurance industry. Employees perceive that organizational culture at PT. Insurance Services Indonesia has a good management system and a fair that is reflected in the characteristics of eight organizational culture, that is the goal, consensus, excellence, unity, achievement, empiricism, intimacy and integrity.Â Keywords: organizational culture, employee perceptions of organizational cultureÂ